2002
DOI: 10.1017/s1539299600012740
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Analogues of Cosmic Dust

Abstract: Abstract. Understanding the properties and the evolution of cosmic dust requires laboratory experiments for measuring basic physical and chemical data and simulating the interaction of dust grains with their cosmic environments. We give a short review of such laboratory experiments using analogue materials of cosmic dust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(91 citation statements)
references
References 8 publications
5
79
0
7
Order By: Relevance
“…Although we could expect the presence of the narrow 11.3 µm emission feature of amorphous SiC grains (optical constants have been taken from Mutschke et al 1999) in stars with C/O ratios close to one, replacing one of the aforementioned dust species with amorphous SiC grains resulted in higher χ 2 values for all spectra. We can confidently state that amorphous silicates, gehlenite and amorphous alumina are necessary to explain the data.…”
Section: Dust Decomposition Toolmentioning
confidence: 99%
“…Although we could expect the presence of the narrow 11.3 µm emission feature of amorphous SiC grains (optical constants have been taken from Mutschke et al 1999) in stars with C/O ratios close to one, replacing one of the aforementioned dust species with amorphous SiC grains resulted in higher χ 2 values for all spectra. We can confidently state that amorphous silicates, gehlenite and amorphous alumina are necessary to explain the data.…”
Section: Dust Decomposition Toolmentioning
confidence: 99%
“…Mutschke et al (1999) have studied the dependence of the spectral appearance of the 11 µm resonance on crystal structure. They concluded that when the crystal is pure, the actual crystal structure is not very important.…”
Section: The Sic Lattice Structurementioning
confidence: 99%
“…First we considered the data as shown before (Laor & Draine 1993). Second we take a rather pure crystal (β-SiC with γ = 10 cm −1 ) according to the equations given by Mutschke et al (1999). Third we consider amorphous SiC as measured by Mutschke et al (1999).…”
Section: The Sic Lattice Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Howa) Electronic mail: alexander.paarmann@fhi-berlin.mpg.de ever, linear optical techniques like reflectivity only provide indirect information, and require differentiation to extract the resonances. 11,12 As one possible solution, nonlinear optical spectroscopy could provide improved sensitivity to critical features in the dielectric response. 13,14 Such studies have been hindered by the sparsity of intense and narrowband laser sources in the mid-IR frequency range and low nonlinear signal levels, such that only few nonlinear optical experiments in the Reststrahl region appear in the literature [15][16][17][18] with no reports for SiC.…”
mentioning
confidence: 99%